The integral of -2x/(2x - 1)^3 is x^2/(2x - 1)^2, we have to find the integral of 4x-3/(2x-1)^3

4x-3/(2x-1)^3

=> 4x/(2x - 1)^3 - 3/(2x - 1)^3

=> -2*(-2x/(2x - 1)^3 - 3/(2x - 1)^3

`int (-2*-2x)/(2x - 1)^3 dx -int 3/(2x - 1)^3 dx`

=> `(-2*x^2)/(2x - 1)^2 - int 3/(2x - 1)^3 dx`

let 2x - 1 = t => dt = 2*dx => 3*dx = (3/2) dt

=> `(-2x^2)/(2x - 1)^2 - (3/2)*int 1/(t^3) dt`

=> `(-2x^2)/(2x - 1)^2 - (3/2)/(-2*t^2)`

substitute t = 2x - 1

=> `(-2x^2)/(2x - 1)^2 + 3/(4*(2x - 1)^2)`

**The required integral is** `((3/4) - 2x^2)/(2x - 1)^2 + C`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.